Finite element analysis with error estimators : an introduction to the FEM and adaptive error analysis for engineering students - Akin, J. E.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier/Butterworth-Heinemann, 2005)
This key text is written for senior undergraduate and graduate engineering students. It delivers a complete introduction to finite element methods and to automatic adaptation (error estimation) that will enable students to understand and use FEA as a true engineering tool. It has been specifically developed to be accessible to non-mathematics students and provides the only complete text for FEA with error estimators for non-mathematicians. Error estimation is taught on nearly half of all FEM courses for engineers at senior undergraduate and postgraduate level; no other existing textbook for this market covers this topic. *The only introductory FEA text with error estimation for students of engineering, scientific computing and applied mathematics *Includes source code for creating and proving FEA error estimators *Complete with homework exercises and supporting website with instructor's solutions manual.
Introduction, Mathematical Premliminaries, Element Interpolation and Local Coordinates, One-Dimensional Integration, Error Estimation for Elliptic Problems, Super-convergent Patch Recovery, Variational Methods, Cylindrical Analysis Problems, General Interpolation, Integration Methods, Scalar Fields, Vector Fields, Index, Solutions Manual.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Finite element method; Structural analysis (Engineering); Error analysis (Mathematics); TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Error analysis (Mathematics); Finite element method; Structural analysis (Engineering); Electronic books